If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = 27 + -4x Solving 5x = 27 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 5x + 4x = 27 + -4x + 4x Combine like terms: 5x + 4x = 9x 9x = 27 + -4x + 4x Combine like terms: -4x + 4x = 0 9x = 27 + 0 9x = 27 Divide each side by '9'. x = 3 Simplifying x = 3
| 3x^2+6=81 | | X^4-3X^3+11X^2-27X+18=0 | | x^2-25x+27=0 | | x^2+25x+23=0 | | 5x-30+4=7x+14-10 | | 48x+20=6(7x+4)+6x-4 | | x^2+-10x+23=0 | | x^2-10x-23=0 | | x^2+10x-23=0 | | m^2+6m+2=0 | | -5(2x-6)+5=-10x+35 | | 0.10(y-4)+0.12y=0.2y-1.5 | | 7+4(3)=1 | | 8(x+9)+3=75 | | 7+4(-3)=1 | | x^2-4x+49=0 | | 4x^2-5x=3 | | x^2-4x+41=0 | | x^2-4x-41=0 | | x^2+4x-41=0 | | 5(2m+5)=65 | | 2*9=6*x | | 13=5+3b-23 | | 24*32= | | 5X^2-31x+30=0 | | 3*15=x*9 | | 1000xq=7.4672 | | x*12=9*16 | | -5-x=2x+3 | | 12*9= | | x*14=4*7 | | 6x^2+26x+20=0 |